Influência da superfície de nanotubos de titânio na resposta bacteriana em implantes biomédicos : revisão sistemática e metanálise - Farina, Georgia Ortega (2021)
Nanotechnology has evolved greatly lately, and in the field of biomedical implants, an alternative treatment of titanium (Ti) surfaces is texturization by electrochemical anodization, generating among other surface textures, Ti nanotubes. These nanotubes appear in the literature as a biologically viable surface, although there are disagreements about the actual cell compatibility for this surface and about its characteristic antibacterial and osteoconductive characteristics. This systematic review aims to investigate possible antibacterial properties of the TI nanotube surface compared to other titanium surface treatments through a systematic literature review. This investigation was performed on PubMed, Lilacs, Embase, Web Of Science, Cinahl, and Cochrane Central bases, as well as manual searches and in the gray literature. The searches resulted in 742 articles, of which 156 followed for full textual reading, where 38 were included in the systematic review and 8 in meta-analysis. The results indicated that of the 30 articles that expressed statistical data, 15 reported results of antibacterial protection using nanotubes, and 15 presented no difference between Ti nanotube and other surface treatments. In meta-analysis, in vivo studies using TI nanotube surfaces presented three times lower bacterial adhesion and proliferation rates. However, considering in vitro studies, there was only a bacterial decrease in studies using Staphylococcus Aureus in the period of 6 hours, and in other methodologies there were no differences between the application of nanotubes or not.